Coordinated control strategy of multiple energy storage power stations supporting black-start based on dynamic allocation. (October 2020) - Li, Cuiping; Zhang, Shining; Li, Junhui; Zhang, Hao; You, Hongfei; Qi, Jun; Li, Jiang
Highlights: A coordinated control strategy of multi-energy storage supporting black-start proposed can solve the erratic black-start. Aiming at the over-charge/discharge, an adaptive multi-energy storage coordinated optimization method is proposed. The power allocation is based on the chargeable/dischargeable capacity and limit power. Control strategy in energy storage power station is combining V/F and P/Q. A black-start model of multiple wind power and energy storage system model is established. Abstract: Due to the disordered charging/discharging of energy storage in the wind power and energy storage systems with decentralized and independent control, sectional energy storage power stations overcharge/over-discharge and the system power is unbalanced, which leads to the failure of black-start. A coordinated control strategy of multi-energy storage supporting black-start based on dynamic power distribution is proposed to solve this issue, which is divided into two layers. The power computational distribution layer divides the energy storage systems (ESSs) into 24 operating modes, according to the working partition of state of charge (SOC) of ESSs. Then, aiming at the power distribution problem of each energy storage power station, an adaptive multi-energy storage dynamic distribution model is proposed. The power tracking control layer adopts the control strategy combining V/f and PQ, which can complete the optimal allocation of the upper the power instructions among energy storage power station and feedback the real-time SOC to the power computational distribution layer. Finally, the proposed control strategy is applied to the black-start system. Compared to the average distribution and the allocation without adaptive control, the improvement degree of SOC of energy storage in the critical interval was increased by 56.5%. In the region with more wind and less water, this method can provide reference and theoretical basis for the wind power participating in the black-start assisted by multi-energy storage stations.